Blivande lärares uppfattningar och förståelse av baskunskap i ekologi i Danmark, Finland och Sverige - Irmeli Palmberg; Gunnar Jonsson; Eila Jeronen; Eija Yli-Panula (Naturfagsenteret, 2025)
Students’ and student teachers’ decreasing interest in and knowledge of science are, according to many national and international assessments, alarming trends in the Nordic countries. This quantitative and qualitative study of student teachers’ knowledge of core concepts and processes in ecology confirms the low level of student teachers’ understanding of these issues, although a majority consider these issues to be basic knowledge for their teacher competencies. Many of the student teachers did not know what biosphere or succession is. They also had difficulties in explaining what a seed contains and what its role is in the plant’s lifecycle. Several student teachers also had difficulties to explain why photosynthesis is important and how it works. The increasing ecological and environmental illiteracy is discussed as one of the implications for teacher education.